2002
DOI: 10.1051/0004-6361:20021491
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the neutron star magnetic field of the two X-ray transients SAX J1808.4–3658 and Aql X–1

Abstract: Abstract.The recently discovered coherent X-ray pulsations at a frequency of ∼400 Hz in SAX J1808.4-3658, together with a measure of the source luminosity in quiescence, allow us to put an upper limit on the neutron star magnetic field, that is B ≤ 5 × 10 8 Gauss, using simple considerations on the position of the magnetospheric radius during quiescent periods. Combined with the lower limit inferred from the presence of X-ray pulsations, this constrains the SAX J1808.4-3658 neutron star magnetic field in the q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 43 publications
8
40
0
Order By: Relevance
“…We can therefore evaluate the magnetic moment, µ, of SAX J1808.4-3658 from our measured value of the spin-down, using the relation µ 2 /(9R 3 CO ) = 2πIν sd , where R CO is the corotation radius. The magnetic field found in this way is B ∼ (3.5 ±0.5) ×10 8 Gauss, perfectly in agreement with previous constraints [13].…”
Section: Sax J18084-3658supporting
confidence: 92%
“…We can therefore evaluate the magnetic moment, µ, of SAX J1808.4-3658 from our measured value of the spin-down, using the relation µ 2 /(9R 3 CO ) = 2πIν sd , where R CO is the corotation radius. The magnetic field found in this way is B ∼ (3.5 ±0.5) ×10 8 Gauss, perfectly in agreement with previous constraints [13].…”
Section: Sax J18084-3658supporting
confidence: 92%
“…the radius at which an object corotating with the NS attains the speed of light; see Ruderman et al 1989;Illarionov & Sunyaev 1975). Di Salvo & Burderi (2003) have shown that a magneto-dipole rotator can easily be active in SAX J1808.4-3658 during quiescence. In fact, for a luminosity in quiescence of ∼5 × 10 31 ergs/s (Campana et al 2002), the NS surface magnetic field should be B < ∼ 0.05 × 10 8 Gauss in order to truncate the disk inside the corotation radius and allow accretion Letter to the Editor onto the NS surface.…”
Section: Irradiation Of the Disk And Companion Star By Rotating Magnementioning
confidence: 99%
“…To this aim we need an estimate of the NS magnetic field in this system. As mentioned above, from a measure of the source luminosity in quiescence and using simple considerations on the position of the magnetospheric radius during quiescent periods, it is possible to estimate an upper limit on the NS magnetic field of B < ∼ 5 × 10 8 Gauss (Di Salvo & Burderi 2003). This, together with the lower limit mentioned above, constrains the SAX J1808.4-3658 NS magnetic field in the quite narrow range (1−5) × 10 8 Gauss.…”
Section: Irradiation Of the Disk And Companion Star By Rotating Magnementioning
confidence: 99%
“…This is true, obviously, only if the binary system was a NS-main sequence binary: in systems where the companion is a white dwarf, and that evolve from short periods towards long periods and do not evolve though a pulsar phase. For instance, the surface magnetic field of the first millisecond X-ray pulsar discovered, SAX J1808.4-3658 [14], has been estimated to be in the range (1 − 5) × 10 8 G [15]. If this system has a MS companion, so that it evolved from longer orbital periods, it cannot be supramassive, as it survived the period gap.…”
Section: Evolution Of Low Mass X-ray Binaries Towards Short Orbital Pmentioning
confidence: 99%